Aspek Kepatuhan KAP BSR Berdasarkan Implementasi Reviu Pengendalian Mutu Perikatan Klien Perbankan - Murti Wijayanti; Maidani Maidani (Akuntansi & Ekonomika, 2022)
This study aims to determine the Public Accounting Firm (KAP) compliance aspects to the Quality Control Standards (SPM) design that has been previously established, through the implementation of Engagement Quality Control Review (EQCR) on banking institutional clients. To maintain the quality audit opinion results, the audit procedures start from pre-engagement, assigning audit process, concluding the review result by quality control reviewer engagement team by filling out checklist on EQCR Sheet document, based on standard containing general client data, financial data, completeness checklist documents, and draft report. The implementation EQCR document result show, from the compliance aspect KAP has carried out audit procedures guided by SPM manual design, although review and monitoring are needed in terms of documentation.